The Impact of Horizontal Mergers on Market Structure: Evidence from the Semiconductor Industry - Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2016)
The U.S. and EU Merger Guidelines strongly emphasize the relevance of the “ease of entry” argument in merger evaluations. Up to now, very little is known empirically about how mergers affect entry and exit, and the resulting number of firms in the markets. We empirically test this aspect of mergers using a comprehensive database that contains detailed firm-level information on mergers, production, and innovation in the dynamic random access memory semiconductor market from 1985 to 2004. Our reduced-form regression results show that mergers dominated by efficiency effects have a negative impact on the number of firms in the product market. Mergers dominated by market power effects result in a higher number of firms than efficiency dominated mergers. Interestingly, we also find that mergers foreclose potential entry in other product markets and reduce the number of firms in related product markets. Finally, our results confirm that postmerger changes in the equilibrium number of firms directly impact market prices.
Keywords: L11; L13; L52; O31; O32; O38; 330; competitive effects; entry; foreclosure; horizontal mergers; market structure